Tuition fee ; Miss Saigon I ; Dalawang Makata [videorecording] - Lazaro, Cheche (Quezon City Probe Productions, 1989)
Students are up in arms against tuition fee hike and other aspects like socialized tuition, subsidized education in sectarian private schools and other financial assistance which they think will be unfair to them. Shows audition process and recruitment of Filipino talents for a London West End production. A story about a concert featuring two poets and two musicians where Filipino poems are put into music.
Tuition fee (14 min.) -- Miss Saigon I (19 min.) -- Dalawang Makata (17 min.)
VHS.
Keywords: Iskolar ng Bayan Program; Socialized Tuition and Financial Assistance Program (STFAP).; University of the Philippines -- Funds and scholarships; Musical ability -- Testing; Music and literature -- Philippines